2017
DOI: 10.11648/j.sjph.20170503.18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alcohol Consumption and Factors Influencing Alcohol Use Among the Youth in Tokorni-Hohoe, Volta Region of Ghana

Abstract: Abstract:Background: Alcohol use still remains a great public health concern. However, the youth are the higher risk group in terms of alcohol consumption and its associate complications. Alcohol consumption among the youth is on the rise and Ghana cannot be exempted due to easy accessibility and availability of alcoholic beverages to the youth. According to Ghana Demographic and Health survey, alcohol consumption is highest among young people between the ages of 15-39 years than other age group; however, litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 13 publications
(26 reference statements)
6
24
3
Order By: Relevance
“…This study made a similar finding that advertisement for alcoholic products has the tendency of influencing about 44.0% to use those products. Though a previous study finding reported a lower percentage (20.3%) on the use of advertisement [24] than the current study, it suggests that advertisements play a vital role in youth alcohol use patterns. Also, the findings of the studies on the risk factors and consequences of alcohol consumption among college students [25],and that on prevalence of alcohol consumption and factors influencing alcohol use among the youth in Tokorni-Hohoe, Volta Region of Ghana [24] correspond to the finding of this study as was found that peer pressure or introduction by friends to alcohol mostly get the youth to drink alcoholic beverages.…”
Section: Discussioncontrasting
confidence: 98%
“…This study made a similar finding that advertisement for alcoholic products has the tendency of influencing about 44.0% to use those products. Though a previous study finding reported a lower percentage (20.3%) on the use of advertisement [24] than the current study, it suggests that advertisements play a vital role in youth alcohol use patterns. Also, the findings of the studies on the risk factors and consequences of alcohol consumption among college students [25],and that on prevalence of alcohol consumption and factors influencing alcohol use among the youth in Tokorni-Hohoe, Volta Region of Ghana [24] correspond to the finding of this study as was found that peer pressure or introduction by friends to alcohol mostly get the youth to drink alcoholic beverages.…”
Section: Discussioncontrasting
confidence: 98%
“…We also highlight increased prevalence of problem drinking among the underage as a result of access to cheap alcohol, particularly, in regard to number of adolescents using alcohol, frequency of use, and increased amounts of alcohol consumed. Similarly, a study in Ghana noted that the prevalence rates of alcohol use among the youth in the area were two times higher than the national average due to ease of availability and access [32]. The Ghanian study adds that the study area is clustered with bars and entertainment places serving alcohol and that these premises lack policy enforcement on underage use, an environment also reported in the current study.…”
Section: Discussionsupporting
confidence: 62%
“…When compared to other African countries, the prevalence of harmful use of alcohol in Nigeria is relatively higher. For example, the prevalence of self-reported binge drinking was 14.1% in South Africa (16) and 16% in Ghana (17), while hazardous users of alcohol were estimated at 12.7% in Uganda (18) and 22.4% in Botswana (19). Despite a declining rate, Nigeria appears to be at the high-end of alcoholic beverage consumption in Africa, as the reported rates are comparable to some estimates in Europe and the Americas, where the prevalence of harmful users ranged from 37-53% (1,68).…”
Section: Discussionmentioning
confidence: 99%
“…There was no study from the North-east. Most studies were conducted in urban settings (17), while rural settings had 5 studies, and mixed settings (a mix of urban and rural dwellers) had 13 studies. Studies were conducted between 1992 and 2017, with most conducted within a one-year period.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation